Mentorship Program as A Productive Teacher Development Program at Sekolah Pelita Harapan in Indonesia - Purba, Rosma Indriana; Putri, Ratna Setyowati; Imelda, Donna (Dinasti International Journal of Management Science, 2020)
A mentorship program is cost-efficient and effective ways to get employees engaged and empowered. The program enables developing talent and increases productivity across the organization. The executive team of Sekolah Pelita Harapan has grown a strong desire to help equipping educational leaders to be effective in their role as educators. It is founded on the belief that an excellent candidate having a background of experience in education and showing strong potential for further leadership development can benefit enormously through the opportunities that mentorship can offer. Through several models of teacher development programs, it was finally confirmed that the mentoring program was an excellent way to develop the teacher's performance. Keywords: mentoring, job shadowing, active application, dialogue, professional reading, self-reflection.